2013
DOI: 10.1186/cc12900
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia during continuous veno-venous hemofiltration is associated with mortality in critically ill patients with acute kidney injury

Abstract: IntroductionThe primary aim of this study was to determine whether hypophosphatemia during continuous veno-venous hemofiltration (CVVH) is associated with the global outcome of critically ill patients with acute kidney injury (AKI).Methods760 patients diagnosed with AKI and had received CVVH therapy were retrospectively recruited. Death during the 28-day period and survival at 28 days after initiation of CVVH were used as endpoints. Demographic and clinical data including serum phosphorus levels were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 25 publications
(29 reference statements)
6
42
2
2
Order By: Relevance
“…It should be underscored that protocol-guided supplementation was sporadically needed, and mainly required in patients already hypophosphatemic at the start of CRRT. Stressing the importance of strategies aimed at preventing, rather than curing, hypophosphatemia, Yang et al [9] recently reported that the ratio of CVVH therapy days with hypophosphatemia to total CVVH days was independently associated with global outcome. The authors highlighted that parenteral phosphate supplementation failed to prevent CVVH-related hypophosphatemia in a majority of the patients underlining that the use of CRRT phosphate-containing solutions could represent a more appropriate option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be underscored that protocol-guided supplementation was sporadically needed, and mainly required in patients already hypophosphatemic at the start of CRRT. Stressing the importance of strategies aimed at preventing, rather than curing, hypophosphatemia, Yang et al [9] recently reported that the ratio of CVVH therapy days with hypophosphatemia to total CVVH days was independently associated with global outcome. The authors highlighted that parenteral phosphate supplementation failed to prevent CVVH-related hypophosphatemia in a majority of the patients underlining that the use of CRRT phosphate-containing solutions could represent a more appropriate option.…”
Section: Discussionmentioning
confidence: 99%
“…Hypophosphatemia is a frequent finding among critically ill patients and its incidence can be further increased by the use of prolonged and intensive modalities of RRT [3][4][5][6][7][8][9] , which achieve a very efficient phosphate clearance [2,13] . Indeed, in 2 large clinical trials, patients receiving the most intensive RRT modalities experienced a higher incidence of hypophosphatemia [4,5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study 9 2-] pl were initiated on RRT with Phoxilium, reflecting the common observation that establishing a 'default' clinical pathway can inadvertently impede the application of clinical judgement. These data reinforce the view that a patient centred RRT strategy is preferable to a 'one size fits all' approach.…”
Section: +mentioning
confidence: 99%
“…8 Hypophosphataemia is independently associated with worse ICU survival; the duration of hypophosphataemia predicts mortality. 9 Phoxilium is a phosphate and potassium containing CRRT fluid, introduced to mitigate the risk of hypophosphataemia and need for potassium supplementation. 10 The composition of Hemosol-B0 and Phoxilium are compared in Table 1 10 It is common practice in most intensive care units to identify a default fluid to be used for CRRT.…”
Section: Introductionmentioning
confidence: 99%